A Phenomenological Grounding of Feminist Ethics. Issue 50 (2nd January 2019) - Daly, Anya
ABSTRACT: The central hypothesis of this paper is that the phenomenology of Merleau-Ponty offers significant philosophical groundwork for an ethics that honours key feminist commitments – embodiment, situatedness, diversity and the intrinsic sociality of subjectivity. Part I evaluates feminist criticisms of Merleau-Ponty. Part II defends the claim that Merleau-Ponty's non-dualist ontology underwrites leading approaches in feminist ethics, notably Care Ethics and the Ethics of Vulnerability . Part III examines Merleau-Ponty's analyses of embodied percipience, arguing that these offer a powerful critique of the view from nowhere, a totalizing God's-eye-view with pretensions to objectivity. By revealing the normative structure of perceptual gestalts in the intersubjective domain, he establishes the view from everywhere . Normativity is no longer deferred to higher authorities such as duty, utility or the valorized virtue, but through the perceptual gestalt it is returned to the perceiving embodied subject. This subject, defined by inherent intersubjectivity, is thereby vulnerable to others and has the capacity for care.